Challenges and benefits of graphic input devices (at the example of graphics tablets) - Kurashkin, O. (ТДАТУ, 2018)
Computer technologies have drastically changed the life of modern society and, of course, had its impact on the art. Nowadays the internet is full of concept art, desktop wallpapers and different kinds of images that have been drawn by professional artists and ordinary users. Therefore, it is unsurprising that digital art has become a common thing and graphic input devices has gained their popularity.
Keywords: popularity; Internet; ordinary users; digital art